2020
DOI: 10.1017/s0144686x20001567
|View full text |Cite
|
Sign up to set email alerts
|

The experience of caring for an older relative in Chile: going beyond the burden of care

Abstract: Care in Chile, as in most Latin American countries, remains largely the responsibility of female family members in informal arrangements with little government support. The analysis of caring for a dependent older person has commonly been approached from the burden of care perspective, focusing on the tasks carried out, the time spent providing care and the negative (burdensome) consequences for the care-giver. This study reveals the daily experiences of family care-givers of older people through a thematic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
7
0
2
Order By: Relevance
“…Smart care systems are often promoted as offering reassurance. This framing aligns with a commonly held association of care with worry 45 and with caring as a relation that involves both labour and emotion 46 and can be an emotional rollercoaster. 47 In the recent COVID-19 pandemic, the challenge of achieving care at a distance and balancing multiple concerns about the safety of those who are cared-for has increased, and we have become acutely conscious that care is more than simply practical labour.…”
Section: Introductionsupporting
confidence: 52%
“…Smart care systems are often promoted as offering reassurance. This framing aligns with a commonly held association of care with worry 45 and with caring as a relation that involves both labour and emotion 46 and can be an emotional rollercoaster. 47 In the recent COVID-19 pandemic, the challenge of achieving care at a distance and balancing multiple concerns about the safety of those who are cared-for has increased, and we have become acutely conscious that care is more than simply practical labour.…”
Section: Introductionsupporting
confidence: 52%
“…Los resultados en general comprueban que las mujeres tienen una vejez con menor calidad de vida, lo que es concordante con la evidencia empírica (11) . Las mujeres han experimentado un curso de vida más complejo, tanto en términos fisiológicos (menopausia) (19) , como sociales debido a las consecuencias vinculadas a las múltiples tareas del cuidado de otras personas (20) .…”
Section: Discussionunclassified
“…However, most empirical evidence regarding this topic is focused on older adults and the implications of religiosity/spirituality for their wellbeing. Older adults in Chile face ageing with higher levels of socioeconomic disadvantages owing to their small pensions, giving rise to precariousness in old age (Moyano-Díaz and Mendoza-Llanos 2020), in addition to a social protection system that is mainly inefficient in the area of health and dependency (Palacios et al 2020). Following this line of argument, a study by Gallardo-Peralta and Sánchez-Moreno (2014) suggested that a combination of religious beliefs and practice was related to a lower incidence of depressive symptoms among older adults.…”
Section: Religiosity In Chile and Its Relation To Mental Illnessmentioning
confidence: 99%